THE INFLUENCE OF LIFESTYLE AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT WITH FINANCIAL LITERACY AS A MODERATING VARIABLE - A. Nur Habibie Jannah; Tenri Sayu Puspitaningsih Dipoatmodjo; Andi Mustika Amin; Anwar Anwar; Annisa Paramaswary Aslam (Jurnal Manajemen, 2026)
Abstract: By using “financial literacy” as a moderator variable, this study aims to investigate the influence of lifestyle and financial attitudes on financial management among students of the 2023-2024 intake of the Management Study Program, Makassar State University. Using a survey methodology, this study adopted a quantitative approach. Through a purposive sampling technique, 250 respondents were selected to participate in the survey. Partial Least Squares - Structural Equation Modeling (PLS-SEM) using SmartPLS 3 was used to evaluate the data obtained from the questionnaire. The research findings indicate that: (1) a person's lifestyle has a significant negative impact on financial management (β = -0.419; p = 0.000); (2) a person's financial attitude has a positive impact on financial management (β = 0.387; p = 0.000); (3) a person's financial literacy has a positive impact on financial management (β = 0.429; p = 0.000); however, (4) a person's financial literacy does not significantly mitigate the impact of a person's lifestyle or financial attitude on financial management. With an R² score of 0.895, the predictive ability of this model is quite high.”Keywords: Lifestyle, Financial Attitude, Financial Literacy, Financial Management